Investigation on superabsorbent polymer as grounding material - Nurul Nadiah, Abdul Halim (2019)
In transmission and distribution network, grounding system contributes significantly for the safety operation of any electrical installation. One of important application of ground enhancing material is the ability reduce the grounding resistance. Bentonite is one of commonly used as ground enhancing material due to its low resistance and ability to retain water. However, there is no production of bentonite in Malaysia whereas kaolinite can be found abundantly. Thus, kaolinite is used as a substitute for bentonite as ground enhancing material. However, the plasticity and water retention are limited as compared to the bentonites. Thus, to enhance the performance of kaolinite in plasticity and resistivity, superabsorbent polymer (SAP) which has high affinity for water, high swelling and have high water retention capacity is added in kaolinite. In this study, three kaolinites are used which are FMC, S300 and Speswhite with addition of 0%, 5% and 10% of SAP. The aims of this study to determine the effect of superabsorbent polymer (SAP) on the plasticity characteristic of kaolinite, to establish soil-water retention curve (SWRC) and to the compare the resistivity of kaolinite with addition of SAP at different percentages. To determine the plasticity of the enhanced kaolinite, physical and chemical properties are conducted. The osmotic and chilled-mirror dew-point methods were used in this study to establish soil-water retention curve (SWRC). Besides that, the resistivity of kaolinites with addition of SAP at different percentages are studied by using soil box method. The obtained results from laboratory tests showed that the plasticity characteristic of enhanced kaolinite is increased. SWRC of kaolinite with addition of SAP are establish and the curve ranging from low suction to high suction value. SWRC shows that water content for all soil samples decrease with increasing of soil suction. The resistivity of FMC, S300 and Speswhite with 10% are 8.80 Ω.m, 6.24 Ω.m and 6.10 Ω.m. Thus, the addition SAP decreases the resistivity of the soil and may be used as ground enhancement material.